2007
DOI: 10.1002/jcp.20959
|View full text |Cite
|
Sign up to set email alerts
|

From the laboratory bench to the patient's bedside: An update on clinical trials with mesenchymal stem cells

Abstract: Mesenchymal Stem Cells (MSCs) are non-hematopoietic multi-potent stem-like cells that are capable of differentiating into both mesenchymal and non-mesenchymal lineages. In fact, in addition to bone, cartilage, fat, and myoblasts, it has been demonstrated that MSCs are capable of differentiating into neurons and astrocytes in vitro and in vivo. MSCs are of interest because they are isolated from a small aspirate of bone marrow and can be easily expanded in vitro. As such, these cells are currently being tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
401
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(423 citation statements)
references
References 71 publications
6
401
0
13
Order By: Relevance
“…MSCs can be considered nonhemopoietic multipotent stem-like cells that are capable of differentiating into both mesenchymal and nonmesenchymal lineages (33). However, there is no specific single marker to clearly define MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can be considered nonhemopoietic multipotent stem-like cells that are capable of differentiating into both mesenchymal and nonmesenchymal lineages (33). However, there is no specific single marker to clearly define MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at present, MSCs are identified through a combination of physical, phenotypic, and functional properties. The classical assay used to identify MSCs is the colony forming unit assay that identifies adherent spindle shaped cells that proliferate to form colonies and can be induced to differentiate into adipocytes, osteocytes, and chondrocytes (33). Because MSC in our study qualify this criteria, we used the term "mesenchymal stem cells" in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, interest in MSCs has already moved from in vitro and animal studies into actual clinical trials in patients [36]. Several phase I-II clinical trials have already shown the safety and efficacy of BM-derived MSCs for enhancing the engraftment of co-transplanted HSCs in patients with hematologic and non-hematologic malignancies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Non-hematopoietic stem cells in the bone marrow are capable of differentiating into a variety of tissue entities, including osteogenic cells of bone tissue [29]. Incubation of mononuclear cells isolated from adult, human bone marrow with mesenchymal stem cell-stimulating medium followed by osteogenic differentiation medium [6,7] gave rise to cells with osteoblastic characteristics, for example mineral deposition (Fig.…”
Section: Egfr/erbb2 Phosphorylation In Supplementary Biological Modelsmentioning
confidence: 99%